Effect of Padina gymnospora biowaste inclusion on in vitro methane production, feed fermentation, and microbial diversity - Mohapatra, Archit; Trivedi, Shraddha; Kolte, Atul P.; Tejpal, Chaluvanahalli S.; Elavarasan, Krishnamoorthy; Vaswani, Shalini; Malik, Pradeep Kumar; Ravishankar, Chandragiri Nagarajarao; Bhatta, Raghavendra (Frontiers in Microbiology, 2024)
In vitro studies were undertaken aiming to study the methane (CH4) mitigation potential of biowaste (BW) of Padina gymnospora at the graded inclusion of 0% (C), 2% (A2), 5% (A5), and 10% (A10) of the diet composed of straw and concentrate in 40:60 ratio. The chemical composition analysis revealed that the BW contained higher crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), and ether extract (EE) than the PF (fresh seaweed, P. gymnospora). The concentration of cinnamic acid, sinapic acid, kaempferol, fisetin p-coumaric acid, ellagic acid, and luteolin in BW was 1.5–6-folds less than the PF. Inclusion of BW decreased (P < 0.0001) CH4 production by 34%, 38%, and 45% in A2, A5, and A10 treatments, respectively. A decrease (P < 0.0001) of 7.5%–8% in dry matter (DM) and organic matter (OM) digestibility was also recorded with the BW supplementation. The BW inclusion also decreased the numbers of total (P = 0.007), Entodinomorphs (P = 0.011), and Holotrichs (P = 0.004) protozoa. Metagenome data revealed the dominance of Bacteroidetes, Proteobacteria, Firmicutes, Actinobacteria, and Fibrobacter microbial phyla. At the phylum level, Euryarchaeota dominated the archaeal community, whereas Methanobrevibacter was most abundant at the genus level. It can be concluded that the inclusion of BW in straw and concentrate based diet by affecting rumen fermentation, protozoal numbers, and compositional shift in the archaeal community significantly decreased CH4 production. Utilization of biowaste of P. gymnospora as a CH4 mitigating agent will ensure its efficient utilization rather than dumping, which shall cause environmental pollution and health hazards.